IMPLEMENTASI PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERDESAAN DI DESA KEBUMEN, KECAMATAN PRINGSURAT, KABUPATEN TEMANGGUNG - Mochamad Hanafi; Hartuti Purnaweni; Margaretha Suryaningsih (Journal of Public Policy and Management Review, 2013)
PNPM-MP is one of the mechanisms of community empowerment program in an effort to accelerate poverty reduction and expansion of employment opportunities inrural areas. Guidelines for the implementation of PNPM-MP contained in the Decree of the Coordinating Minister for People's Welfare No. 25 of 2007. PNPM-MP implementation in various places showed varying results. Pringsurat District Temanggung Regency, is one of the districts that implement the PNPM Mandiri since the beginning of the name of the PPK in 2003. In this district, the biggest beneficiary in 2012 is Kebumen Village.Implementation of PNPM-MP at Kebumen Village has been good since it follows the stages of Directive Technical Operations. Constraints faced which are deteriorationof physical activities and clogged installment loans are now almost resolved. Planning should take into consideration in the implemention based on community activities, siteconditions and seasons. At the time of eligibility verification, character of the people who apply should be considered, as well as their ability and discipline to pay.